Examining the enabling and barrier factors to nursing staff involvement of children in care activities - Kwaku Richard Bawah; Wahab Osman; Diana Pireh; Millicent Kala; Vivian Afoko; Feruza Abdulai (International Journal of Africa Nursing Sciences, 2024)
Background: Children’s rights to participate in decisions and activities of their lives have been well documented. Due to varied challenges, the implementation of children’s rights to healthcare involvement has not been fully achieved. The unsuccessful implementation could be attributed to factors originating from parents/caregivers, health professionals, children, policymakers, and the healthcare system. Therefore, investigating the barriers and enabling factors to the implementation of children’s rights to healthcare involvement is critical. Objective: This study therefore examined the enabling and barrier factors to nursing staff involvement of children in care activities. Methods: An institutional-based cross-sectional design was used to conduct the study at the Evangelical Church of Ghana Hospital, Kpandai. With a total census sampling technique, all nursing staff members providing care to paediatric patients were invited to participate in the study due to the relatively small number of nursing staff. A total of 97 nursing staff members finally participated. An adapted Patient Participation Questionnaire was used for the data collection. Descriptive and inferential analyses were done at p < 0.05 and considered statistically significant. Results: Out of 116 nursing staff, 97 (83.6% response rate) participated. The frequently reported barrier factors to nurses' involvement of children in care activities were staff uncertainty about children’s competence (78.4%), nurses’ limited knowledge about children’s rights (66%), and children’s age and maturity (65%). On the other hand, regular sensitization of nurses about children’s rights recorded more than 90% of responses as an enabling factor. Nurses who perceived children not to be mature were -1.175 (AOR = 0.309; 95% CI: 0.145–0.658) times less likely to involve children in their care. Nurses who frequently communicated with children were 0.660 (AOR = 1.935; 95% CI: 1.098–3.411) times more likely to involve children in their care. Conclusion: Nurses' involvement of children in care is largely influenced by their limited knowledge about children’s rights and policies. Therefore, training modules involving children’s rights should be included in the curricula of students in the medical field, while in-service training seminars organized regularly for practicing nurses.